2019
DOI: 10.1080/14659891.2019.1614234
|View full text |Cite
|
Sign up to set email alerts
|

The link between childhood trauma and dissociation in frequent users of classic psychedelics and dissociatives

Abstract: Background: Childhood trauma severity is associated with the level of subsequent substance use as well as with the self-reported severity of dissociation. Classic psychedelics and dissociatives target neurotransmitter systems thought to be involved in the onset of dissociative symptoms and may evoke severe and long-lasting symptoms of depersonalization in some users. However, it is currently unclear whether drug use puts people with a history of childhood trauma at higher risk of developing dissociative sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…It is possible that the modest changes in methylation in our sample was due in part to the minimal trauma history of many of our participants. Our overall CTQ scores are in line with previous research utilising the CTQ in non-clinical samples (80,81), and is lower than expected from clinical samples (82)-this is despite our depressed subsample not having a significantly different CTQ score to our non-depressed subsample.…”
Section: Epigeneticssupporting
confidence: 90%
“…It is possible that the modest changes in methylation in our sample was due in part to the minimal trauma history of many of our participants. Our overall CTQ scores are in line with previous research utilising the CTQ in non-clinical samples (80,81), and is lower than expected from clinical samples (82)-this is despite our depressed subsample not having a significantly different CTQ score to our non-depressed subsample.…”
Section: Epigeneticssupporting
confidence: 90%
“…Further efforts should be devoted to identifying biological biomarkers and psychological predictors of psychedelicinduced subjective effects (such as rostral ACC thickness), as well as dissociation, negative experiences, and psychoses. This could help identify patients more likely to encounter challenging experiences (such as those with high neuroticism, emotional instability, and family history of psychosis, bipolar disorders, and childhood trauma) and implement adequate strategies to maximize therapeutic improvement while minimizing potential biological and psychological short-and longterm side effects (Barrett et al, 2017;Thal et al, 2019;Lewis et al, 2020).…”
Section: Potential Long-term Physical Side Effects Inmentioning
confidence: 99%
“…This has similar theoretical connotations to the Simonsson et al finding that a major life event prior to the experience was predictive of degree of enduring difficulty, in terms of antecedent life events being formative to psychedelic outcomes [ 16 ]. Previous research has identified a strong link between childhood trauma and developing dissociative symptoms following classic psychedelic use [ 46 ] as well as increased vulnerability to the development of psychiatric disorders [ 47 ].…”
Section: Discussionmentioning
confidence: 99%